The Impact of Covid -19 Pandemic on Students Learning at Universitas Muhammadiyah Gombong - Nurlaila, Nurlaila; Sari, Wahyu Monika; Utami, Wuri (Prosiding University Research Colloquium, 2022)
Covid-19 is a global health problem. When the number of cases of Covid-19 increased, the government imposed a study from home policy. This has resulted in various impacts on learning in higher education. This study aims to determine the impact that occurs in the online learning process of health students at Universitas Muhammadiyah Gombong during the Covid-19 pandemic. The study uses a qualitative method with a phenomenological approach. Data collection was carried out by online interviews using handphones with health study program students of Universitas Muhammadiyah Gombong (10 participants) who were taken by cluster random sampling. Data analysis using thematic analysis assisted by OpenCode 4.02 software. The results show 5 themes, namely changes in activity due to the pandemic, psychological changes for students, lectures during the pandemic, online lecture constraints, and student coping in the face of the Covid-19 pandemic. The impact of the Covid-19 pandemic has resulted in changes in daily activities caused many obstacles during online learning and boring, saturated and feeling uncomfortable.